2011
DOI: 10.5194/acp-11-1405-2011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of upstream source influences on total gaseous mercury observations in Ontario, Canada

Abstract: Abstract. Hourly total gaseous mercury (TGM) concentrations at three monitoring sites (receptors) in Ontario were predicted for four selected periods at different seasons in 2002 using the Stochastic Time-Inverted Lagrangian Transport (STILT) model, which transports Lagrangian air parcels backward in time from the receptors to provide linkages to the source region in the upwind area. The STILT model was modified to deal with Hg deposition and high stack Hg emissions. The model-predicted Hg concentrations were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…2005; Durnford et al, 2010). Point Petre is a rural site that is affected by regional pollution episodically (Blanchard et al, 2002;Kellerhals et al, 2003;Temme et al, 2007;Wen et al, 2011). Thus, although the latitudinal difference is not the only difference between these three stations, it is likely the most important difference.…”
Section: Atmospheric Mercurymentioning
confidence: 99%
“…2005; Durnford et al, 2010). Point Petre is a rural site that is affected by regional pollution episodically (Blanchard et al, 2002;Kellerhals et al, 2003;Temme et al, 2007;Wen et al, 2011). Thus, although the latitudinal difference is not the only difference between these three stations, it is likely the most important difference.…”
Section: Atmospheric Mercurymentioning
confidence: 99%
“…A number of studies have used these data to evaluate CMAQ-Hg (Bash, 2010;Bullock and Brehme, 2002;Bullock et al, 2008Bullock et al, , 2009Gbor et al, 2006Gbor et al, , 2007Lin et al, 2007;Lin and Tao, 2003;Pongprueksa et al, 2008;Sunderland et al, 2008;Vijayaraghavan et al, 2007), and other atmospheric chemistry models that include mercury (Cohen et al, 2004;Holmes et al, 2010;Sanei et al, 2010;Seigneur et al, 2003;Selin and Jacob, 2008;Vijayaraghavan et al, 2008). Until recently, most studies that evaluate model estimates of ambient mercury compare with Total Gaseous Mercury (TGM) and/or Hg 0 (Gbor et al, 2006(Gbor et al, , 2007Holmes et al, 2010;Lin and Tao, 2003;Lohman et al, 2008;Selin et al, 2007;Soerensen et al, 2010;Wen et al, 2011).…”
Section: T Holloway Et Al: An Assessment Of Atmospheric Mercury In mentioning
confidence: 99%
“…Other studies have identified alternative sources such as Taconite mining (Han et al, 2005) as well as melting snow and local mobile sources . In addition to anthropogenic sources, several studies identified the importance of natural sources, including vegetation sources (Wen et al, 2011) and the Atlantic Ocean .…”
Section: Introductionmentioning
confidence: 99%